Chloroplast redox state changes mark cell‐to‐cell signaling in the hypersensitive response. Issue 2 (1st September 2022) - Lukan, Tjaša; Županič, Anže; Mahkovec Povalej, Tjaša; Brunkard, Jacob O.; Kmetič, Mirjam; Juteršek, Mojca; Baebler, Špela; Gruden, Kristina
Summary: Hypersensitive response (HR)‐conferred resistance is associated with induction of programmed cell death and pathogen spread restriction in its proximity. The exact role of chloroplastic reactive oxygen species and its link with salicylic acid (SA) signaling in HR remain unexplained. To unravel this, we performed a detailed spatiotemporal analysis of chloroplast redox response in palisade mesophyll and upper epidermis to potato virus Y (PVY) infection in a resistant potato genotype and its transgenic counterpart with impaired SA accumulation and compromised resistance. Besides the cells close to the cell death zone, we detected individual cells with oxidized chloroplasts further from the cell death zone. These are rare in SA‐deficient plants, suggesting their role in signaling for resistance. We confirmed that chloroplast redox changes play important roles in signaling for resistance, as blocking chloroplast redox changes affected spatial responses at the transcriptional level. Through spatiotemporal study of stromule induction after PVY infection, we show that stromules are induced by cell death and also as a response to PVY multiplication at the front of infection. Overall induction of stromules is attenuated in SA‐deficient plants.